Conjugate natural convection flow of a nanofluid with oxytactic bacteria under the effect of a periodic magnetic field - Geridonmez, B. Pekmen; Öztop, Hakan Fehmi (Elsevier, 2022)
Conjugate natural convection flow in a cavity is numerically investigated under the effect of a periodic magnetic field. The cavity has a vertical thermally conducting solid block and a part where the nanofluid flows. The most left wall of the cavity is the hot one and the most right one is the cold one. The problem is considered as two-dimensional and time independent, and a vertical periodic magnetic field is taken into account. Nanoparticle is chosen as SiO2 and the host fluid is water. Inside of the nanofluid, the existence of oxytactic microorganisms is also assumed. Brownian motion and thermophoresis effects are also considered in governing equations. The influence of pertinent parameters biconvection Rayleigh number Rb = 1-100, Lewis number Le = 1-20, Peclet number Pe = 0.1-5, Brownian motion parameter Nb = 0.1-1, thermophoresis parameter Nt = 0.1-1, Hartmann number Ha = 0-100, period of periodic magnetic field angstrom = 0.1-1, amplitude of periodic magnetic field A = 0.1-1 and conductivity ratio kr = 0.1-10 are examined on fluid flow, heat and mass transfer. Numerical results in view of isolines as well as average Nusselt and Sherwood numbers are presented. Conductivity ratio kr = 10 has more impact on convective heat and mass transfer. Convective mass transfer depends on the vertical wall considered as solid-fluid interface or the right cold vertical wall. It is an increasing function of Le, Pe, Ha, Nt and Nb and decreasing function of Rb in interface.
Keywords: Periodic magnetic field; Natural convection; Heat transfer; SiO2-water; Radial basis functions; Bioconvection